Algorithm for the Implementation of Manometry and Ph-Impedansometry in the Management of Patients with Refractory Gastroesophageal Reflux Disease (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Gastroesophageal reflux disease (GERD) is a widespread disease that has a significant impact on the quality of life of patients and is a leading risk factor for the development of esophageal adenocarcinoma. Currently, proton pump inhibitor therapy (PPI) is the basic treatment for patients with GERD, but 1/3 of patients show resistance to the prescribed therapy.Currently, 24-hour pH-impedancemetry and high-resolution esophageal manometry are the most informative diagnostic methods in patients resistant to PPI therapy. These methods allow timely recognition of the causes of the refractory course of GERD, differential diagnosis with other nosologies, timely correctionadminister therapy individually for each patient.